Knowledge and Community Preparedness for Flood Disaster in Sempaja Timur Village, Samarinda City - Cornelia Dede Yoshima Nekada; Linda Herawati; Nazwar Hamdani Rahil (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Indonesia is a country prone to flooding because it has large rivers and is located between two largest oceans in the world, the Indian Ocean and the Pacific Ocean. The country is also one of the areas prone to natural hazards and natural disasters. Community’s knowledge greatly influences the community's concern and attitude to be alert and ready for disaster. Objective: This study aims to find out the correlation between knowledge and community preparedness for flood disaster in Sempaja Timur Village, Samarinda City. Method: This study uses a cross-sectional approach with a total sample of 155 households in in the East Sempaja Village, Samarinda City, selected through an technique was multistage random sampling. Data were analysed in Somer's test. Results: Respondents with a level of knowledge in the moderate category as much as 63.9%. Respondents who have a level of preparedness for floods with a very prepared category are 98.7%. Conclusion: There was a significant correlation between knowledge and community preparedness for flood disaster in Sempaja Timur Village, Samarinda City (p = 0,00).